WISC-IV performance of children with Chronic Tic Disorder, Obsessive-Compulsive Disorder and Attention-Deficit/Hyperactivity Disorder: results from a German clinical study - Sina Wanderer; Veit Roessner; Anja Strobel; Julia Martini (BMC, 2021)
Abstract Background Chronic Tic Disorder (CTD), Obsessive-Compulsive Disorder (OCD) and Attention-Deficit/Hyperactivity Disorder (ADHD) are complex neuropsychiatric disorders that frequently co-occur. The aim of this study was to examine WISC-IV performance of a clinical cohort of children with CTD, OCD and/or ADHD. Methods N = 185 children aged 6 to 17 years from Germany with CTD, OCD and/or ADHD were examined with the WISC-IV that comprises four index scores (VCI: Verbal Comprehension Index, PRI: Perceptual Reasoning Index, WMI: Working Memory Index, PSI: Processing Speed Index) and a Full Scale Intelligence Quotient (FSIQ). WISC-IV profiles of children with CTD-only, OCD-only, ADHD-only, CTD+ADHD, CTD+OCD and CTD+OCD+ADHD were compared with the WISC-IV norm (N = 1650, M = 100 and SD = 15) and among each other. Results Unpaired t-tests revealed that children with ADHD-only showed significant lower PSI scores, whereas children with CTD-only and OCD-only had significant higher VCI scores as compared to the German WISC-IV norm. One-way ANOVA revealed that children with ADHD-only showed significant lower WMI scores as compared to children with CTD+OCD. Conclusions We were able to confirm previous evidence on WISC-IV profiles in ADHD in a German clinical sample and contribute new findings on cognitive performance in children with (non-)comorbid CTD and OCD that have to be seen in light of the study's limitations.